KONSTRUKSI IDENTITAS SEKELOMPOK MAHASISWA SASTRA INDONESIA UNIVERSITAS ANDALAS MELALUI KEGIATAN MINUM KOPI: TINJAUAN CULTURAL STUDIES - Hawa, Andina Meutia; Pratiwi, Dyani Prades; Saniro, Roma Kyo Kae (Universitas Islam Sumatera Utara, 2023)
This paper discusses how the identity of a group of students from the Indonesian Literature Study Program at Andalas University, Padang, is constructed through drinking coffee in a coffee shop. Drinking coffee is one activity that is being loved by young people, especially amidst the massive emergence of coffee shops in various parts of the city of Padang. The number of coffee shops in the city of Padang influences the people's culture of drinking coffee. According to Baudrillard's theory of hyperreality, drinking coffee does not only contain use and exchange values, but also contains sign and symbolic values. The activity of drinking coffee is not just quenching thirst and delaying sleepiness, but is also done for the purpose of having fun and strengthening identity. In addition, there is an act of looking at each other and being seen between male students and female students in their behavior drinking coffee in coffee shops. Through filling out a questionnaire conducted by a group of students, it was shown that visiting coffee shops did not necessarily give rise to coffee connoisseurs, but rather as a form of lifestyle for early subjects and popular cultural practices, visiting coffee shops was shown as a fun activity, as well as strengthening one's identity in the world. virtual and real world.